Uberization as a rupture of path dependence: the case of taxi companies - Newton da Silva Miranda Júnior; Denise Rossato Quatrin; Valmir Emil Hoffmann (Revista Eletrônica de Ciência Administrativa, 2022)
The competitiveness brought by application companies, such as Uber, to the individual transport market is often emphasized. However, an important question remains unanswered: what are the strategies implemented by taxi companies, in terms of improvements and innovations, to remain competitive in this market? This study sought to answer this question by identifying how uberization causes a break in the path dependence of taxi companies, according to the assumptions of the Path Dependence Theory and the Competitive Strategy. In this regard, this research is a case study from the Federal District state, one of the pioneers in uberization, from Brazil. For this purpose, secondary qualitative data were collected via documentary research in local newspapers of great circulation. In total, 178 reports were collected, covering the period from 2008 to 2017, which were analyzed through the Content Analysis and Procedural Data Analysis. The results suggest that, before the entrance of application companies, taxi companies implemented self-sustaining innovations. After uberization, taxis started to adopt disruptive innovations aimed at passengers, breaking the dependence of the current trajectory.